2009
DOI: 10.3340/jkns.2009.45.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Apoplexy Presenting as Isolated Third Cranial Nerve Palsy with Ptosis : Two Case Reports

Abstract: Pituitary apoplexy is a clinical syndrome caused by an acute ischemic or hemorrhagic vascular accident involving a pituitary adenoma or an adjacent pituitary gland. Pituitary apoplexy may be associated with a variety of neurological and endocrinological signs and symptoms. However, isolated third cranial nerve palsy with ptosis as the presenting sign of pituitary apoplexy is very rare. We describe two cases of pituitary apoplexy presenting as sudden-onset unilateral ptosis and diplopia. In one case, brain magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 15 publications
1
24
0
6
Order By: Relevance
“…symptom of pituitary tumor apoplexy. Won-Jun et al [9] describe two cases of pituitary apoplexy presenting as sudden onset unilateral ptosis and diplopia due to an isolated oculomotor nerve palsy. Both cases exhibited complete resolution of symptoms in the early postoperative period.…”
Section: Diplopiamentioning
confidence: 98%
See 2 more Smart Citations
“…symptom of pituitary tumor apoplexy. Won-Jun et al [9] describe two cases of pituitary apoplexy presenting as sudden onset unilateral ptosis and diplopia due to an isolated oculomotor nerve palsy. Both cases exhibited complete resolution of symptoms in the early postoperative period.…”
Section: Diplopiamentioning
confidence: 98%
“…Patients experience diplopia as dictated by specific cranial nerve involvement; the oculomotor nerve (typically pupil-involving) accounts for 50% of patients with cranial nerve palsies, probably due to its supero-lateral course through the cavernous sinus in the same axial plane as the pituitary gland, leaving it more susceptible to the lateral pressure from an expanding mass [1 , 6,9,13].…”
Section: Diplopiamentioning
confidence: 99%
See 1 more Smart Citation
“…9,14,15 In the majority of these cases, no precipitating factors were found. The precipitating factors include 2 cases of mild head injury 16 and 1 each of Sheehan's syndrome 5 and anticoagulation (present case). In contrast, Sibal et al 12 found that 40% of pituitary apoplexy cases had a precipitating factor.…”
Section: Diagnosis and Discussionmentioning
confidence: 89%
“…Various degrees of cranial nerve palsy can result from compression of cranial nerves III, IV, V, and VI, with an expanding mass in the cavernous sinus. 5 However, isolated oculomotor nerve palsy without visual acuity or field deficits as the presenting sign of pituitary apoplexy is rare (Table 1). …”
Section: Diagnosis and Discussionmentioning
confidence: 99%